Singer and the New Animal Liberation - Francesco Allegri (Relations, 2024)
The new edition of Peter Singer’s “Animal Liberation” gives the author the opportunity to take stock of the improvements in the conditions of non-human animals, particularly in the European Union, and to emphasize the importance of the dissemination of this volume for their achievement. In addition, the article returns to discuss Singer’s theoretical approach to animal ethics, highlighting its various oscillations and some critical issues. The author, while distancing himself from utilitarianism (the moral theory advocated by Singer), points out that a good part of Singer’s moral reflection about non-human animals is convincing, so his contribution contains more lights than shadows.